2008
DOI: 10.1158/1078-0432.ccr-07-1440
|View full text |Cite
|
Sign up to set email alerts
|

The Mitogen-Activated Protein/Extracellular Signal-Regulated Kinase Kinase Inhibitor AZD6244 (ARRY-142886) Induces Growth Arrest in Melanoma Cells and Tumor Regression When Combined with Docetaxel

Abstract: Purpose: Disseminated melanoma is highly therapy resistant. The finding that 66% of melanomas harbor the activating BRAF V600E mutation has raised expectations for targeting the Ras/RAF/mitogen-activated protein (MAP)/extracellular signal-regulated kinase (ERK) kinase (MEK)/ERK pathway in melanoma. This study addresses the anti-melanoma activity of the MEK inhibitor AZD6244 (ARRY-142886). Experimental Design: We recently have shown that growing melanoma cells as threedimensional collagen-implanted spheroids en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 210 publications
(184 citation statements)
references
References 34 publications
12
170
0
2
Order By: Relevance
“…Mutated BRAF activates the MEK-ERK kinase pathway, which is an essential regulator of cell growth, differentiation, cell cycle progression, and oncogenic transformation (Sebolt-Leopold & Herrera 2004). BRAF-targeting compounds and MEK inhibitors, designed to disrupt the RAF-MEK-ERK pathway have been developed and are currently being tested in clinical trials for treatment of various human cancers (Beeram et al 2005, Gray-Schopfer et al 2007, Haass et al 2008. Several studies have shown that BRAF mutant cancer cells may be susceptible to anti-cancer drugs, such as AZD6244 (used to treat melanoma) (Smalley & Flaherty 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Mutated BRAF activates the MEK-ERK kinase pathway, which is an essential regulator of cell growth, differentiation, cell cycle progression, and oncogenic transformation (Sebolt-Leopold & Herrera 2004). BRAF-targeting compounds and MEK inhibitors, designed to disrupt the RAF-MEK-ERK pathway have been developed and are currently being tested in clinical trials for treatment of various human cancers (Beeram et al 2005, Gray-Schopfer et al 2007, Haass et al 2008. Several studies have shown that BRAF mutant cancer cells may be susceptible to anti-cancer drugs, such as AZD6244 (used to treat melanoma) (Smalley & Flaherty 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The interpretation of these results is somewhat hindered by the poor pharmacological properties of this agent. Similar G1-phase growth arrest results have been observed with allosteric MEK inhibitors, such as U0126, PD0325901 and AZD6244, suggesting that inhibition of the MAPK pathway in melanoma is largely cytostatic Solit et al, 2006;Haass et al, 2008). Activating BRAF V600E mutations are also known to occur in subsets of thyroid and colon carcinomas (Davies et al, 2002), and similar to melanoma, the presence of the mutation also predicts for sensitivity to MEK inhibition (Solit et al, 2006;Leboeuf et al, 2008).…”
Section: Preclinical Studies On Braf/mek Inhibitorsmentioning
confidence: 66%
“…Analysis of patient samples pre-and posttreatment revealed that sorafenib incompletely inhibited ERK phosphorylation. This observation may be significant as preclinical studies show that complete pathway inhibition is needed to induce cell cycle arrest (Solit et al, 2006;Haass et al, 2008). In the single-agent phase II trials with sorafenib, the common toxicities were hypertension and hand-foot syndrome, consistent with the toxicities described with inhibitors of VEGF signalling.…”
Section: Clinical Studies On Braf/mek Inhibitorsmentioning
confidence: 77%
See 2 more Smart Citations